Cormac McCarthy : A complexity theory of literature - Cooper, Lydia R., 1980- (Book collections on Project MUSE., 2021)
Cormac McCarthy: A complexity theory of literature offers the first sustained analysis of complexity science in McCarthy's literary works. McCarthy's fiction makes a significant case study demonstrating how literature can help us imagine and grapple with complex systems and crises, from global economic inequality to climate change.